Handbook of Complementary Methods in Education Research. - Green, Judith L. (Taylor & Francis, 2006)
Published for the American Educational Research Association by Routledge. The Handbook of Complementary Methods in Education Research is a successor volume to AERA's earlier and highly acclaimed editions of Complementary Methods for Research in Education. More than any book to date (including its predecessors), this new volume brings together the wide range of research methods used to study education and makes the logic of inquiry for each method clear and accessible. Each method is described in detail, including its history, its research design, the questions that it addresses, ways of using t.